العوامل المؤثرة على سلوك المستهلك وعلاقتها بالقرار الشرائي: (دراسة ميدانية على الشباب السوري في المرحلة الجامعية) - الحموي فواز صالوم; حمدان مهند رامز (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تكمن أهمية المستهلك في الدور الذي يلعبه في نشاط الشركات والمؤسسات التي تقوم بتقديم منتجاتها وخدماتها له، فالاستراتيجيات التسويقية الناجحة تعتمد على فهم رجال التسويق بشكل عميق لأبعاد السلوك الشرائي للمستهلكين، ويتطلب ذلك دراسة سلوكه لمعرفة أكثر العوامل تأثيراً فيه والتي تتنوع بين العوامل الاجتماعية -الحضارية - الثقافية- العمر- الجماعة المرجعية....إلخ. لذلك عمدنا إلى إعداد هذا البحث الهادف إلى توضيح أهمية العوامل المختلفة في سلوك المستهلك ودورها وعلاقتها بالقرار الشرائي، وقد طبق هذا البحث على عينة من المستهلكين في المرحلة الجامعية، وتم التوصل إلى مجموعة من الاستنتاجات والتوصيات منها: أهمية متابعة التغير في أنماط سلوك الفرد، وضرورة تجزئة السوق وفقاً للمتغيرات الحضارية، والتركيز على الاهتمام بالمنافع التي تقدمها السلعة من حيث السعر والجودة، وتصميم الإعلانات بشكل علمي. The importance of consumer lies in the role that he/she is playing in the companies’ and institutions’ activities which offer their products and services for him/her. The successful marketing strategies depend on the deep understanding of the dimensions of consumers’ purchasing behavior by marketers. This requires a study of this behavior to know the most effective factors which vary between social, civilization-related, and cultural factors, as well as age, and referential group. For that we intended to prepare this research which aims to clarify important role of different factors in the consumers’ behavior and their relation to the purchasing decision, This research has been applied on a sample of consumers in the academic level. A set of conclusions and recommendations has been reached: The importance of watching changes in individual’s behavior patterns, the necessity to divide the market according to civilization-related changes and concentrating on utilities which offered by the product concerning quality, price and scientific planning of advertising.